Importance of intercultural communication in the teaching of foreign language (German language) (Eurasian Journal of Philology Science and Education, 2016)
The article deals with the methods and of formation of intercultural competence to prepare competitive and competent professionals who meet the requirements of education in communication in a foreign language. Communication requires not only the knowledge of a foreign language but also a good knowledge of traditions and cultural particularities of the target language . Getting acquainted with the language and culture of another country, we receive the life experience, information on social norms, values of foreign countries, thus we enrich our spiritual experience. Proverbs reflect the cultural and spiritual formation of the studied language. During the research period there were identified characteristics and methods of proverb usage to form intercultural competence of students in learning of foreign language.
Keywords: intercultural communication; the formation of competencies; proverbs and sayings; foreign language teaching; interrelated understanding; cultural fund.